2005
DOI: 10.1111/j.1600-0404.2005.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Mosaicism and phenotype in ring chromosome 20 syndrome

Abstract: Ring chromosome 20 [r(20)] syndrome is a rare chromosomal disorder characterized by epilepsy, mild to moderate mental impairment, and malformation. Patients generally show mosaicism in 1-100% of lymphocytes with r(20). We report here a patient with r(20) syndrome who exhibited mild phenotype with the small ratio of mosaicism (13%) with r(20). Although previous small-scale studies concluded that the mosaicism ratio was unrelated to clinical phenotype, our reassessment of all 57 reported cases has revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 21 publications
8
44
1
Order By: Relevance
“…The phenotype of this case shared many clinical features of previously reported ring chromosome 20 cases [Nishiwaki et al, 2005], especially the form of epilepsy (Table I).…”
Section: Clinical Reportmentioning
confidence: 56%
See 3 more Smart Citations
“…The phenotype of this case shared many clinical features of previously reported ring chromosome 20 cases [Nishiwaki et al, 2005], especially the form of epilepsy (Table I).…”
Section: Clinical Reportmentioning
confidence: 56%
“…These observations suggested that specific genes on chromosome 20 are responsible for the typical seizure phenotypes in ring chromosome 20. Nine cases with supernumerary mosaic ring chromosome 20 with two normal 20's and one or two additional ring 20's have been reported [Nishiwaki et al, 2005]. Seven cases had one additional ring chromosome 20, and two cases carried one to two additional rings.…”
Section: Seizure Disorder and Ring Chromosomementioning
confidence: 97%
See 2 more Smart Citations
“…Second, due to problems with chromatid separation, ring chromosomes are mitotically unstable, and give rise to a spectrum of secondary chromosomal defects including monosomy, double rings, and marker chromosomes [Vogel and Motulsky, 1997]. Various cell lines coexist within the patient in a mosaic state, and the phenotype can depend on the composition and frequency of mosaicism, and its distribution in different tissues [Nishiwaki et al, 2005]. Because of the instability of the ring chromosomes it was proposed that carriers, irrespective of the chromosome involved, suffer from a universal ''ring syndrome'' [Kosztolanyi, 1987].…”
Section: Discussionmentioning
confidence: 99%